Genetic Predisposition to Bleeding during Oral Anticoagulant Therapy: Evidence for Common Founder Mutations (FIXVal-10 and FIXThr-10) and an Independent CpG Hotspot Mutation (FIXThr-10) - Oldenburg, J.; Kriz, K.; Wuillemin, W. A.; Maly, F. E.; von Felten, A.; Siegemund, A.; Keeling, D. M.; Baker, P.; Chu, K.; Konkle, B. A.; Lämmle, B.; Albert, T.; the Study Group on Hereditary Warfarin Sensitivity (Thrombosis and Haemostasis, 2001)
The recent discovery of five patients with coumarin sensitive FIX-variants due to a missense mutation in the FIX propeptide, either Ala-10Val or Ala-10Thr, has highlighted a novel type of genetic predisposition to bleeding during oral anticoagulant therapy (OAT). In the present study, we report six additional patients with such FIX variants. Haplotype analysis of FIX polymorphisms revealed a founder effect in the five German and Swiss patients with the Val-10 variant. Also, four Thr-10 variants detected in Germany, Switzerland and Great Britain derived from a common founder. Two Thr-10 variants from USA showed an independent de novo origin at a CpG dinucleotide that in general represents a mutation hotspot. These findings implicate the existence of additional subjects with corresponding variants in the populations of various countries. Even though the rare occurrence of these variants does not justify a general aPTT screening during OAT, it is recommended to monitor each bleeding event during OAT in males in order to exclude a genetic predisposition to bleeding by means of the following testing strategy: a) aPTT-testing in each bleeding complication of male patients during OAT, b) if aPTT is disproportionately prolonged, determination of FIX:C, and c) if FIX:C is disproportionately decreased as compared to FII:C, FVII:C and FX:C, sequencing of exon 2 of the FIX gene. This strategy will provide a cost-effective and safe procedure to identify patients that carry the FIX variants. Moreover, such a strategy accumulates data about the prevalence of these FIX mutations in a given population.
Keywords: Factor IX gene; warfarin sensitivity; oral anticoagulation; founder effect